THEORETICAL PRINCIPLES OF COMPANY PERSONNEL DEVELOPMENT MANAGEMENT - Boryshkevych , I. I.; Hoi , N. V.; Zhuk , O. I. (The actual problems of regional economy development, 2024)
Current domestic companies face a number of challenges, such as the instability of the economic situation, war in the country, rapid technological changes, as well as changes in consumer preferences. In order to address these challenges, companies that recognize the significance of employee development actively implement training and development strategies. These strategies aim to enhance employees' skills, foster the acquisition of new knowledge, and facilitate adaptation to evolving demands and technologies. Staff development plays a crucial role in enhancing efficiency and productivity, improving the quality of work and customer service, and boosting employee satisfaction and loyalty. Moreover, it aids in reducing employee turnover and attracting and retaining talented professionals. This article explores the essence of personnel development within a company. The interpretations of the concept of “personnel development” by various scholars are examined. It is established that personnel development involves a purposeful and systematic approach to enhancing employees' knowledge and competencies. Three main approaches to employee development within a company are characterized: process-oriented, system-oriented, and function-oriented. The primary objective of personnel development in a company is to ensure that employees possess the necessary knowledge and competencies to achieve predetermined goals. The components of personnel development within a company include personnel sourcing, adaptation, professional training, evaluation and certification, as well as career planning. The article also delves into the main approaches to managing personnel development within a company. Specifically, three approaches are characterized: personal development-oriented, social development-oriented, and professional development-oriented. The stages of managing the employee development process within a company encompass planning, implementation, and monitoring. The article further explores the objectives and advantages of effective personnel development management. Various characteristics are employed to classify personnel development methods, including the location of study, level of innovation, number of participants, level of involvement, level of production integration, and duration.